The effect of firm-specific factors on the market reaction to dividend change announcements: new evidence from Europe - Vieira, Elisabete F. Simões (2007)
The dividend policy is one of the most debated topics in the finance literature. According to the dividend signalling hypothesis, which has motivated a significant amount of theoretical and empirical research, dividend change announcements trigger share returns because they convey information about management’s assessment on firms’ future prospects. Consequently, a dividend increase (decrease) should be followed by an improvement (reduction) in a firm’s value. However, some studies have not supported the hypothesis of a positive relationship between dividend change announcements, and the subsequent share price reaction, such as the ones of Lang and Litzenberger (1989), Benartzi, Michaely and Thaler (1997), Chen, Firth and Gao (2002), Abeyratna and Power (2002) and Vieira (2005). Furthermore, some authors found evidence of a significant percentage of cases where share prices reactions are opposite to the dividend changes direction, like the works of Asquith and Mullins (1983), Benesh, Keown and Pinkerton (1984), Born, Mozer and Officer (1988), Dhillon and Johnson (1994) Healy, Hathorn and Kirch (1997), and, more recently, Vieira (2005). Consequently, we try to identify firm-specific factors that contribute in explaining the adverse market reaction to dividend change announcements. Globally, our evidence suggests that only for the UK sample we have firm-specific factors influencing the market reaction to dividend change announcements. We conclude that the UK firms with a negative market reaction to dividend increase announcements have, on average, higher size, lower earnings growth rate and lower debt to equity ratios.